Hydrothermal stability of hydrogen permselective amorphous silica membrane synthesized by counter diffusion chemical vapor deposition method - Miyajima, K.; Eda, T.; Nair, Balagopal; Honda, S.; Iwamoto, Y. (2013)
Hydrogen-permselective amorphous silica membranes were synthesized by the counter diffusion chemical vapor deposition (CD-CVD) method using hexamethyldisiloxane as amorphous silica source, and the effect of the mesoporous intermediate layer and the CD-CVD process temperature on the hydrothermal stability of the amorphous silica membranes were studied. A mesoporous amorphous silica intermediate layer with a mean pore size of 20 nm was synthesized on a macroporous a-Al2O3 support. Under a hydrothermal condition at 500°C by maintaining steam-nitrogen mixed gas, the mesoporous amorphous silica intermediate layer exhibited an excellent stability, while the conventional sol gel-derived mesoporous ?-Al2O3 intermediate layer showed considerable degradation. The improvement in the hydrothermal stability at 500°C of the hydrogen-permselective amorphous silica membrane was successfully achieved by high-temperature synthesis at 700°C of the CD-CVD-derived microporous amorphous silica membrane on the porous a-Al2O3 support having the hydrothermally stable amorphous silica intermediate layer. Further study on the microstructure observations and evaluation of activation energies for the hydrogen permeation through the amorphous silica membranes were performed, and the results are shown and discussed from a viewpoint to achieve further hydrothermal stability improvement for further applications to hydrogen production processes. © 2013 The Ceramic Society of Japan. All rights reserved.